Endogenous growth, downward wage rigidity and optimal inflation - Mirko Abbritti; Agostino Consolo; Sebastian Weber (European Central Bank (ECB), 2021)
Standard New Keynesian (NK) models feature an optimal inflation target well below two percent, limited welfare losses from business cycle fluctuations and long-term monetary neutrality. We develop a NK framework with labour market frictions, endogenous productivity and downward wage rigidity (DWR) which challenges these results. The model features a non-vertical long-run Phillips curve between inflation and unemployment and a trade-off between price distortions and output hysteresis that change the welfare-maximizing inflation level. For a plausible set of parameters, the optimal inflation target is in excess of two percent, a target value commonly used across central banks. Deviations from the optimal target carry welfare costs multiple times higher than in traditional NK models. The main reason is that endogenous growth and DWR generate asymmetric and hysteresis effects on unemployment and output. Price level targeting or a Taylor-rule responding to the unemployment rate can handle better the asymmetric and hysteresis effects in our model and deliver significant welfare gains. Our results are robust to the inclusion of the effective lower bound on the monetary policy interest rate.
Keywords: E24; E3; E5; O41; J64; 330; Endogenous Growth; Monetary Policy; Optimal Inflation Target; Downward Wage Rigidity; Monetary Policy Invariance Hypothesis; Zero LowerBound